2013
DOI: 10.1063/1.4807906
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Si-doping and resultant cation vacancy formation on the luminescence dynamics for the near-band-edge emission of Al0.6Ga0.4N films grown on AlN templates by metalorganic vapor phase epitaxy

Abstract: Luminescence dynamics for the near-band-edge (NBE) emission peak at around 250 nm of c-plane Si-doped Al0.6Ga0.4N films grown on AlN templates by low-pressure metalorganic vapor phase epitaxy were studied using deep ultraviolet time-resolved photoluminescence and time-resolved cathodoluminescence spectroscopies. For the films with the Si-doping concentration, [Si], lower than 1.9 × 1017 cm–3, the doping lessened the concentration of cation vacancies, [VIII], through the surfactant effect or the aid of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 50 publications
6
97
0
Order By: Relevance
“…35 For instance, positron annihilation spectroscopy experiments have shown evidence that complexes between vacancies and donor impurities exist and are associated with specific near-UV emissions in AlN and AlGaN. [35][36][37] Previous theoretical studies of point defect complexes in the nitrides have investigated the stability of vacancy complexes, 28 impurity complexes involving Mg, 24,25,38,39 and nearest neighbor pairs (e.g., C N -C Al , Si N -Si Al ). 40 One DFT study using standard functionals examined the binding energy of neutral nC N -Si Al (n ¼ 1-4) complexes in AlN as compared to the neutral C N and Si Al isolated point defects.…”
mentioning
confidence: 99%
“…35 For instance, positron annihilation spectroscopy experiments have shown evidence that complexes between vacancies and donor impurities exist and are associated with specific near-UV emissions in AlN and AlGaN. [35][36][37] Previous theoretical studies of point defect complexes in the nitrides have investigated the stability of vacancy complexes, 28 impurity complexes involving Mg, 24,25,38,39 and nearest neighbor pairs (e.g., C N -C Al , Si N -Si Al ). 40 One DFT study using standard functionals examined the binding energy of neutral nC N -Si Al (n ¼ 1-4) complexes in AlN as compared to the neutral C N and Si Al isolated point defects.…”
mentioning
confidence: 99%
“…Chichibu et al [18] have reported that the intensity of NBE emission (I NBE ) of Al 0.6 Ga 0.4 N:Si films on AlN template decreased clearly with the increase of the doping concentration of Si, when the doping concentration of Si was elevated to above 1 Â 10 18 cm À 3 . The intensity ratio of the NBE emission to the deep level emission (I NBE /I deep ) even abruptly decreased to nearly 0.01 when the doping concentration of Si reached 4.0 Â 10 18 cm À 3 .…”
Section: Resultsmentioning
confidence: 98%
“…However, when the Si doping was divided into multi-periods and each was followed by an in-situ thermal annealing, the electron concentration reached to 1.1 Â 10 19 cm À 3 and the mobility was promoted to 4.8 cm 2 /V s for sample B. It is known that Al vacancies (V Al ) are the major vacancy defects in Al x Ga 1 À x N alloys [18], the substitutional impurities (Si Al ) can be formed by the thermal annealing. First, the in-situ thermal annealing at higher temperatures cannot only reduced the defects including dislocations, but provided the energy to ionize the donors and drove them into the substitutional sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute the broad band ranging from 3 eV to 4 eV to silicon, oxygen and carbon related defects and their complexes. Their intensities are not strongly influenced by the layer thickness, despite the roughening of the surface which could have indicated a deterioration of the crystal quality and increase in structural defects.…”
Section: Resultsmentioning
confidence: 99%